PROSPEK PASAR SAGU - Satria Astana; Hariyatno Dwiprabowo; Triyono Puspitodjati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Based on the demand potential,sago starch has a good prospect in both domestic and international domestic market, sago starch will be largely absorbed by the domestic High Frutose syroupe (HFS) industry. A new plant of total capacity as much as 198.600 tonnes per annum is being considered by the indonesian Government. In interna tional market, the demand potential of sago is promising. The developing countries alone will be facing the cereai, defisit of 67 million tonnes in 1990 and 105 million tonnes in 2000. Sago starch is expected to contribute a sizeable quantityto overcome these defisits.